Pengaruh Pengesahan Omnibus Law terhadap Abnormal Return, Trading Volume Activity dan Security Return Variability - Nacida Yahya; Gendro Wiyono; Alfiatul Maulida (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to analyze the effect of the Omnibus Law’s approval on the Indonesian capital market’s reaction. The population used in this study is Kompas100 Index stock, the sampling technique used in this study was non-probability sampling with saturated samples. Data were taken using the documentation technique by amazing and evaluating historical data from various sources. The results of this study stating approval of the Omnibus Law do not have a positive and significant effect on abnormal return and security return variability, while approval of the Omnibus Law had a positive and significant on the trading volume activity. The findings can imply the imvestor on their decision by contemplating the information on the stock market. Keywords: Omnibus Law, Abnormal Return, Trading Volume Activity, Security Return Variability